BALANCE BETWEEN GTM AND CLT IN THE CLASSROOM - Xonto‘rayeva, Yulduz Kenjaboy qizi; Yavkacheva, Mohlaroyim Azizbek qizi; Yugay , Evgeniya Viktorovna (INTERNATIONAL CONFERENCE DEDICATED TO THE ROLE AND IMPORTANCE OF INNOVATIVE EDUCATION IN THE 21ST CENTURY, 2022)
Throughout the history of evolution of teaching foreign languages there were debates over which methods were the most effective. However, modern educational system does not label any method as the best or the worst, but searches the ways to implement them together in order them to form a concord. This article illustrates the benefits of GTM and CLT when they are implemented in the classroom together.